Colour perception changes with basic colour word comprehension - Forbes, SH; Plunkett, K (Wiley, 2023)
Recent work has investigated the origin of infant colour categories, showing pre-linguistic infants categorise colour even in the absence of colour words. These infant categories are similar but not identical to adult categories, giving rise to an important question about how infant colour perception changes with the learning of colour words. Here we present two novel paradigms in which 12- and 19-month-old participants learning English as their first language were assessed on their perception of colour, while data on their colour word comprehension were also collected. Results indicate that participants' perception of colours close to the colour category boundaries dramatically change after colour word learning. The results highlight the shift made from infant colour categories to adult-like linguistically mediated colour categories that accompanies colour word learning.